2021
DOI: 10.1007/s11701-021-01346-w
|View full text |Cite
|
Sign up to set email alerts
|

Robotic surgery training during general surgery residency: a survey comparing attitudes towards a robotic training curriculum within general surgery, urology, and OBGYN residents and attendings

Abstract: General surgery residents are increasingly exposed to robotic surgery during their training. However, there is no standardized robotic educational curriculum across United States residency programs. Prior to implementing a robotic surgery curriculum, we surveyed our residents and attendings to ascertain their attitude towards robotic surgery training in residency. An anonymous survey was distributed to all general surgery, obstetrics and gynecology (OBGYN), and urology residents, and their respective attending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…postulated that a shift toward robotic procedures performed by senior residents or attending surgeons leads to a delay in residency training [ 29 ]. Another recent investigation revealed that young residents are interested in robotic surgery and would appreciate an early implementation of robotic surgery during residency [ 30 ]. A study from the United States showed that in many surgical residency programs, a robotic curriculum was already introduced in recent years [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…postulated that a shift toward robotic procedures performed by senior residents or attending surgeons leads to a delay in residency training [ 29 ]. Another recent investigation revealed that young residents are interested in robotic surgery and would appreciate an early implementation of robotic surgery during residency [ 30 ]. A study from the United States showed that in many surgical residency programs, a robotic curriculum was already introduced in recent years [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is useful and a positive outcome of simulator training given that it allows for learning of skills within realistic simulation prior to the operating room, increasing learner and faculty confidence in capability. The benefit of implementation has been acknowledged by residents and attending staff alike from multiple subspecialties, as in evident in a survey study performed by Carroll et al in which 100% of residents surveyed believed a formal curriculum should be implemented within their respective programs [ 18 ]. Similarly, an updated survey of program directors across the country showed agreement in 83% of respondents that robotic-assisted surgery training provided a net benefit to general surgery residents [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since its introduction in the 2000s, the use of robotic platforms has substantially expanded in general surgery including its application in colorectal surgery [ 5 ]. The wristed instruments with 7 degrees of articulation, tremor reduction, and 3-dimensional high-definition view were considered a significant advance over laparoscopy particularly when operating in the pelvis.…”
Section: Introductionmentioning
confidence: 99%